Egg Laying Decisions in Drosophila Are Consistent with Foraging Costs of Larval Progeny - Schwartz, Nicholas U. (Public Library of Science, 2012)
Decision-making is defined as selection amongst options based on their utility, in a flexible and context-dependent manner. Oviposition site selection by the female fly, Drosophila melanogaster, has been suggested to be a simple and genetically tractable model for understanding the biological mechanisms that implement decisions [1]. Paradoxically, female Drosophila have been found to avoid oviposition on sugar which contrasts with known Drosophila feeding preferences [1]. Here we demonstrate that female Drosophila prefer egg laying on sugar, but this preference is sensitive to the size of the egg laying substrate. With larger experimental substrates, females preferred to lay eggs directly on sugar containing media over other (plain, bitter or salty) media. This was in contrast to smaller substrates with closely spaced choices where females preferred non-sweetened media. We show that in small egg laying chambers newly hatched first instar larvae are able to migrate along a diffusion gradient to the sugar side. In contrast, in contexts where females preferred egg laying directly on sugar, larvae were unable to migrate to find the sucrose if released on the sugar free side of the chamber. Thus, where larval foraging costs are high, female Drosophila choose to lay their eggs directly upon the nutritious sugar substrate. Our results offer a powerful model for female decision-making.